Personalized approach in the management of women with heart failure with preserved ejection fraction and carbohydrate metabolism disorders - L.R. Petrovska; I.O. Kostitska; T.R. Petrovskyy; R.V. Petrovskyy (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. The progression of heart failure (HF) in individuals with carbohydrate metabolism disorders is one of the many fatal complications among comorbid conditions. It is found that the risk of developing HF in women with diabetes mellitus (DM) is five times higher than in those without it. Due to both heterogeneity and syntropy of etiopathogenetic mechanisms of occurrence, the prevalence of DM and HF is increasing in the world population, and delayed treatment potentiates a poor prognosis. The main task of the medical community is undoubtedly the early diagnosis of heart failure with preserved ejection fraction (HFpEF) and the prescription of justified pathogenetic treatment, especially for individuals with prediabetes/type 2 diabetes mellitus (T2DM). Therefore, the main strategy for the treatment of comorbid pathology is the use of patient-oriented approaches taking into account gender characteristics and the search for alternative ways to achieve glycemic goals safely in individuals with HFpEF and carbohydrate metabolism disorders. The purpose of the study was to examine the results of a 12-week course of treatment with metformin alone or a combination of metformin and dapagliflozin with an emphasis on the correction of functional iron deficiency in women with HFpEF and prediabetes/T2DM. Materials and methods. Sixty female individuals who met the study criteria were examined and divided into two groups: group I (n = 30) — HFpEF and prediabetes; group II (n = 30) — HFpEF and T2DM. Depending on the pathogenetic therapy, patients in both study groups were randomized to subgroup A (IA: n = 15; IIA: n = 15), who received metformin alone (at a daily dose of 500–2000 mg) and subgroup B (IB: n = 15; IIB: n = 15) — metformin (500–2000 mg/day) in combination with dapagliflozin (10 mg/day). According to the design of the scientific study, all patients at the beginning and after 12 weeks of therapy underwent assessment of basic anthropometric data, a set of laboratory examinations, clinical and instrumental diagnosis. Results. In the IB group, the high effectiveness of a 12-week course of pathogenetic therapy was confirmed according to the carbohydrate metabolism indicators (glycated hemoglobin (HbA1C): ∆–10.67 %, p < 0.001) with a significant increase in left ventricular ejection fraction (∆+7.73 %, p < 0.001) compared to the women receiving metformin alone (∆–1.53 %, p > 0.5). When using the studied treatments in individuals with HFpEF and prediabetes, it was confirmed a reliable normalization of glycemic control and a high chance (odds ratio 0.12, 95% confidence interval 0.011–1.339) of preventing the risk of T2DM. The effectiveness of additional prescription of dapagliflozin together with metformin in patients with HFpEF and carbohydrate metabolism disorders confirms the safe correction of functional iron deficiency with a significant increase of transferrin saturation (IB/IIB groups: ∆+38.51 %, p < 0.001/∆+ 29.59 %, p < 0.001); content of serum iron (IB/IIB groups: ∆+14.93 %, p < 0.001/∆+ 10.07 %, p < 0.5) and a tendency towards compensatory hypoferritinemia. On the background of a 12-week course of combination therapy (daily dose of metformin is 2000 mg, dapagliflozin is 10 mg), there was a comparable decrease in carbohydrate metabolism indicators in the IIB group (IIA/IIB groups: HbA1C after treatment: ∆–1.75 %/∆–10.67 %, p < 0.001, respectively) and an improvement of laboratory and instrumental parameters of HFpEF (IIA/IIB groups after treatment: NT-pro-BNP content: ∆–5.96 %, p < 0.05/∆–13.65 %, p < 0.001; left ventricular ejection fraction: ∆+1.38 %/∆+9.00 %, p < 0.001, respectively). Conclusions. The proposed personalized approaches to the treatment of women with HFpEF and prediabetes have prognosis-modifying effect on HF manifestations and effective glycemic control. Timely prescription of dapagliflozin together with metformin to women with HFpEF and carbohydrate metabolism disorders contributes to the safe correction of functional iron deficiency. As a result of receiving combined pathogenetic therapy, there was a comparable compensation of carbohydrate metabolism indicators and improvement of laboratory and instrumental signs of HF in patients with HFpEF and T2DM. These conclusions contribute to a better understanding of the therapeutic potential of dapagliflozin and the prevention of polypharmacy in comorbidity.